Position vector of spacelike biharmonic curves in the Lorentzian Heisenberg group Heis3 - Turhan, Essin; Koerpinar, Talat (Sciendo, 2011)
In this paper, we study space like biharmonic curves in the Lorentzian Heisenberg group Heis(3). We show that spacelike biharmonic curves are general helices. We characterize position vector of spacelike biharmonic general helices in terms of their curvature and torsion.
Keywords: Biharmonic curve; general helices; Heisenberg group